Acute limb ischemia in COVID-19 patients and its rehabilitation: a case series from a tertiary care hospital in Central India - Harchandani, Rohit; Kela, Manoj; Bawa, Abhishek; Rathod, Ashish; Wajid, Sheikh; Gupta, Apoorv; Chaphekar, Rohan; Bhandari, Vinod (International Journal of Research in Medical Sciences, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a highly transmissible and infectious virus. It belongs to the family coronavirus and it is a single strand positive sense virus. There are many theories which relate to the origin and transmission of this virus and hence the virus has been tagged with many names according to various taxonomical guidelines. The conventional clinical spectrum of this infection includes cough, fever, dyspnea, anorexia and gastrointestinal symptoms. It has been seen during the course of this disease that there are also some properties relating this virus to the hypercoagulability in the disease spectrum. The cases involving arterial and venous thromboembolism are not rare. This case series is a collection on three such cases from the red zone (zone separated for COVID-19 infected patients) of a tertiary care hospital in central India which showcase acute limb ischemia in patients infected with SARS-CoV-2.